Impact of Game-Based and Think-Pair-Share Pedagogies on Teacher Trainees’ Performance in Science - Parker, Joseph (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of the study was to determine the impact of game-based and think-pair-share pedagogies on teacher trainees’ performance in science. This study adopted an action research design. The study was carried out in Enchi College of Education in the Western North Region of Ghana. Stratified, simple random and systematic sampling techniques were used to select 80 respondents (40 males and 40 females) for the study.  The instruments used for the data collection were test. The findings of the study revealed that, the mean value of post-test and pre-test results level 100 respondents exposed to game-based pedagogy differ significantly. The findings of the study again revealed that, the mean value of post-test and pre-test results level 100 respondents exposed to think-pair-share pedagogy differ significantly. This implies that, the game-based pedagogy and think-pair-share pedagogy had impact on teacher trainees’ performance in science. It was therefore recommended that creative approaches such as game-based pedagogy and think-pair-share pedagogy should be adopted by science tutors in Enchi College of Education for effective teaching and learning of science.